A Review on Processing, and Applications of Nanocomposites - El Hawary, Asmaa; Hasan, Salma; El Sttar, Reem Abd; Mohamed, Seif; Bassyouni, M. (Journal of Composites and Biodegradable Polymers, 2019)
In recent decades, nanocomposites have become one of the centers of interest in research and industrial fields because they provide electrical, mechanical and optical enhancements significantly superior to conventional microscale composites which makes them suitable for a wide range of applications in electronics industry, packaging industry, biomedical research and much more. This review thoroughly discusses three types of nanocomposites: ceramic-matrix nanocomposites (CMNCs), polymer-matrix nanocomposites (PMNCs), and metal-matrix nanocomposites (MMNCs) and provides an overview of the most common fillers, methods of preparation, challenges, properties and applications.